MAthE the Game: A Serious Game for Education and Training in News Verification - Anastasia Katsaounidou; Lazaros Vrysis; Rigas Kotsakis; Charalampos Dimoulas; Andreas Veglis (MDPI AG, 2019)
During the last years, there has been a growing multidisciplinary interest in alternative educational approaches, such as serious games, aiming at enhancing thinking skills and media literacy. Likewise, the objective of this study is to present the design and the development of an educational web application for learning the necessary steps towards the detection of bogus content, according to the fact-checking procedures. The game presents news articles, which have to be characterized as fake or real by the players. During the effort to reach the correct decision, the players can use tools and practices for identifying relevant information regarding the clues, which frame a news story (title, date, creator, source, containing images). After presenting the progress of interface design and development, this paper reports the results of a randomized online field study (n = 111), which provides some preliminary evidence. Specifically, it is validated that the game can raise awareness, teach about authentication tools, and highlight the importance of patterns that include evidence regarding the authenticity of articles. Additionally, thorough discussion was conducted within a media class (n = 35) to receive useful feedback/evaluation about the offered utilities and their usability. The findings suggest that educational games may be a promising vehicle to inoculate the public against misinformation.